Knowledge and attitude toward dental trauma first aid among a sample of emergency room personnel across Saudi Arabia - Sharat Chandra Pani; Rayan M Eskandrani; Khalid Al-Kadhi; Abdullah Al-Hazmi (Wolters Kluwer Medknow Publications, 2015)
Background: Traumatic dental injuries (TDIs) have been reported to be a low priority of emergency room (ER) personnel; however there have been increased calls from across the world to train ER personnel in the provision of dental trauma first aid (DTFA). Aim: The aim was to measure the knowledge and attitude of a sample of ER physicians, nurses and emergency medical technicians (EMTs) from across Saudi Arabia regarding DTFA. Materials and Methods: A structured questionnaire was modified from previously existing questionnaires on the topic. A stratified, cluster sample was designed by randomly selecting hospitals across four regions of Saudi Arabia. A total of 150 questionnaires was distributed to all the ER personnel of these hospitals of which 146 completed responses were received. Results: The overall knowledge scores ranged from 0 to 6 out of 7 (mean score 2.88 ± 0.55). Surgeons had the best knowledge about DTFA while EMTs had the lowest knowledge. Nurses had the most positive attitude toward the management of DTFA. Regression models showed that specialty of the personnel and previous education about DTFA significantly influenced knowledge while witnessing a TDI was the only factor that significantly influenced attitude. Conclusion: Overall knowledge of DTFA among ER personnel across the sampled regions of Saudi Arabia is low.